2017
DOI: 10.1128/iai.00438-17
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17A Aggravates Middle Ear Injury Induced by Streptococcus pneumoniae through the p38 Mitogen-Activated Protein Kinase Signaling Pathway

Abstract: Acute otitis media (AOM) is one of the most common bacterial infectious diseases in children aged 2 to 7 years worldwide. We previously demonstrated that interleukin-17A (IL-17A) promotes an acute inflammatory response characterized by the influx of neutrophils into the middle ear cavity during Streptococcus pneumoniae-induced AOM. In general, the inflammatory response is viewed as an effector that frequently causes local tissue damage. However, little is known about the pathogenic effects of IL-17A in AOM. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Previous studies have established the involvement of the IL-17 pathway in the pathogenesis of OME. 9 While IL-17 exerts its local proinflammatory effects, it is systemically produced and adjusts many types of cells, including fibroblasts, macrophages, endothelial cells, and epithelial cells to mobilize the immunological cells to the inflammatory site. 18 The present study suggests that IL-17 exacerbates OME by stimulating ROS (MPO, MDA, NO, and CT), through finding a significantly higher level of ROS in patients with OME than in their healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have established the involvement of the IL-17 pathway in the pathogenesis of OME. 9 While IL-17 exerts its local proinflammatory effects, it is systemically produced and adjusts many types of cells, including fibroblasts, macrophages, endothelial cells, and epithelial cells to mobilize the immunological cells to the inflammatory site. 18 The present study suggests that IL-17 exacerbates OME by stimulating ROS (MPO, MDA, NO, and CT), through finding a significantly higher level of ROS in patients with OME than in their healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have established the involvement of the IL-17 pathway in the pathogenesis of OME. 9 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The same group found that IL-17A also induces ME injury since IL-17A knockout (KO) mice display less severe pathological changes in their ME and lower pro-inflammatory cytokine and myeloperoxidase (MPO) levels. Furthermore, the group showed that neutrophil MPO production is mediated by the p38 MAPK signaling pathway (Wang et al, 2017).…”
Section: Genes Involved In Inflammatory Responses In Ommentioning
confidence: 99%